HUBUNGAN INDEKS MASA TUBUH (IMT) DENGAN NYERI DISMENORE PADA MAHASISWI PROGRAM STUDI SARJANA KEPERAWATAN DAN PROFESI NERS FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Juliantini, Komang Trisna Putri; Devi, Ni Luh Putu Shinta; Damayanti, Made Rini (Coping: Community of Publishing in Nursing; Vol 9 No 6 (2021): Desember 2021, 2021)
Menstruation is part of the process of growth and physical development experienced by young women. Dysmenorrhea is one of the most common complaints during menstruation. Pain severity is felt to interfere with activity. Various factors can affect dysmenorrhea, one of which is the nutritional status that plays a role in influencing the growth and function of the reproductive organs. Nutritional status can be measured through body mass index (BMI). The purpose of this study was to determine the relationship between BMI and dysmenorrhea pain in the 2017 PSSKPN FK Unud students. Measuring instruments used by namely scales, standard microtouise, and pain scale observation using the Numerical Rating Scale (NRS).This study was a descriptive correlational study with a cross-sectional approach. The sample in this study amounted to 49 people selected using consecutive sampling. Based on the results of the static test, it was found that there was a relationship between BMI and dysmenorrhea pain in female students, analyzed using Spearman Rank, showed a significantly weak and positive pattern of relationship between BMI and dysmenorrhea pain (p = 0.005; ? = 0.05; rs = 0.396). This shows that the higher the BMI, the more severe the pain of dysmenorrhea felt by female students. It is expected that nursing students will increase awareness in terms of maintaining the body's nutritional status so that it can prevent dysmenorrhea. Keywords: BMI, Nursing Student, Pain Dysmenorrhea